Hybrid Reversible Digital Image Processing Using Fibonacci-Pell-Based Encryption and Transform Domain Techniques - Pothineni Rishik, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Reverse watermarking in image digital processing is now essential where high-fidelity image reconstruction and authentication are required, like in medical imaging and archiving in a legal setting. The current paper proposes the latest innovative hybrid watermarking algorithm that combines Integer Wavelet Transform (IWT) and Singular Value Decomposition (SVD) to a dual layer of the Fibonacci and Pell numbers based encryption algorithm. The watermark is then encrypted with a two-layer XOR process to provide a little upgrade in security against illegitimate extraction due to the deterministic behaviour of the Fibonacci and Pell sequences. The encrypted watermark is spread in the host image's low-frequency sub-bands through multi-level IWT and SVD, making it imperceptible and robust. Using an experimental setup, it has been proved that the existing methods do not perform well; therefore, the proposed scheme is highly efficient compared to the existing techniques in some of the critical parameters such as Peak Signal-to-Noise Ratio (PSNR), Structural Similarity Index (SSIM), and Normalized Correlation Coefficient (NCC). The original image and the watermark can also be retrieved without loss, demonstrating the system's complete reversibility. The tradeoff of this hybrid model consists of increased resistance to typical attacks on images in the processing domain, combined with conservation of image quality. These factors can be used in secure and reversible watermarking.
Keywords: Hybrid Reversible Watermarking; Fibonacci-Pell-Based Image Encryption; Integer Wavelet Transform (IWT); Singular Value Decomposition (SVD) Embedding; Secure Medical Image Authentication